Diabetes mellitus and arterial hypertension in patients with chronic renal failure on dialysis: An integrative review (Research, Society and Development, 2021)
Objective: To analyze the scientific evidence about the diagnosis of Hypertension (SAH) and Diabetes Mellitus (DM) in patients with chronic renal failure on dialysis in Brazil. Method: An integrative literature review was conducted, conducted by a reviewer in the PubMed, Web of Science, SciELO and LILACS databases. Eligibility criteria wer Established: original observational studies written in Portuguese, English or Spanish, which assessed the prevalence of the association between DM and SAH in the Brazilian population. Result: Diabetic nephropathy (DN) is a chronic complication of diabetes that affects Brazilians in about 20 to 30% of people with DM, being responsible for approximately half of the cases of renal failure in dialysis patients in Brazil. Arterial or primary hypertension is described as one of the most prevalent causes of ESRD. A low agreement percentage (15%) for SAH was noted.